Interaction between soil microbiome and nematode activity in soybean crop - Barros, Felipe Martins do Rêgo (2023)
The nematode community is an important component of soil biodiversity, which has a wide range of ecological functions, from nutrient cycling to plant parasitism. Although much effort has been made to describe the plant-parasitic nematode communities associated to soybean crop, little is known about the interactions between nematodes and soil microbiome. Here, two experiments under controlled conditions and analyses of 178 soil samples collected from the main soybean producing areas in Brazil, in four different biomes (Amazon Rainforest, Atlantic Rainforest, Cerrado, and Pampa), were used to assess the relationships between soil bacterial communities and (plant-parasitic and free-living) nematode communities in soybean crop. Soil bacterial and total nematode communities were analysed by sequencing of the 16S rRNA and 18S rRNA genes, respectively, while plant-parasitic nematode communities were analysed by light microscopy. Furthermore, we investigated the influence of soil physicochemical properties on the plant-parasitic nematode community and microbial activity by analysing 216 soil samples collected from no-till soybean crops. Our experimental results demonstrated the suppressive effect of soil bacterial diversity against Meloidogyne javanica in soybean plants and highlighted some groups of bacteria potentially antagonistic to this plant-parasitic nematode, such as Pseudomonas spp. and Microbacterium spp. Our sampling results showed significant negative correlations between population density of Pratylenchus sp. and relative abundance of several bacterial genera that naturally occur in soybean cultivated soils, such as Streptomyces and Paenibacillus, which are known antagonists of plant-parasitic nematodes. Our results also showed that the total nematode community in soils cultivated with soybean in Brazil is predominantly composed of the orders Rhabditida, Tylenchida, Dorylaimida, Triplonchida and Enoplida, while the plant-parasitic nematode community is predominantly composed of the genera Meloidogyne, Pratylenchus, Heterodera, Rotylenchulus, Helicotylenchus, Scutellonema, and Xiphinema. We also observed a positive correlation between the total nematode richness (predominantly composed by free-living nematodes) and soybean yields, which highlights the positive importance of the free-living nematode community in maintaining and increasing grain productivity. In addition, our results demonstrated that the clay content and the soil pH are the main soil physicochemical properties modulating the plant-parasitic nematodes community in soybean cultivated soils under the no-till system and the soil organic matter content and the pH are the main properties modulating the microbial activity in those soils. Our study is the first to provide insights into the interactions between soil bacterial diversity and nematode communities in soybean crop in Brazil, which may be useful for the design of new strategies to manage these organisms and for the development of new biological products based on bacteria potentially antagonistic to plant-parasitic nematodes.